A 2020 Vision for food, agriculture, and the environment in South Asia: a synthesis - Rosegrant, Mark W.; Malik, Sohail (International Food Policy Research Institute, 1995)
The 2020 vision for South Asia aims to (1) ensure the minimum food and nutrition needs of the population through entitlement programs and income-augmenting agricultural technologies that are environmentally friendly; (2) eliminate severe malnutrition and extreme poverty; (3) ensure comprehensive food and nutritional security at the family level, including an adequate supply of food to meet quantitative and nutritional requirements, acknowledging that policies may vary from country to country, depending on the resources available to the country; (4) arrest environmental degradation and improve the conservation of natural resources for enhanced sustainability and productivity of agriculture; and (5) strengthen or establish linkages among related sectors to promote agricultural diversification and to improve the quality of life.